Analisis Kualitas Air Tanah dan Air Permukaan pada Land Application di PT. X - Ria Hikmarina; Guntar Marolop; Marhadi Marhadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The application of land application as a palm oil mill effluent (POME) management method aims to reduce environmental pollution while improving soil fertility. However, this practice has the potential to affect groundwater and surface water quality in the surrounding area. This study aims to analyze groundwater and surface water quality in the land application area of PT. X, Muaro Jambi Regency, and to evaluate its compliance with environmental quality standards. A descriptive quantitative method was employed by collecting wastewater samples at the WWTP outlet, surface water samples from the Sekawan River (upstream and downstream), and groundwater samples from monitoring and control wells. The analyzed parameters included pH, BOD, COD, TSS, and ammonia (NH₃). The results indicate that the wastewater quality at the WWTP outlet meets the applicable standards. However, groundwater and surface water around the land application area show a tendency toward increased BOD, COD, TSS, and ammonia levels, although most values remain below the permissible limits according to Government Regulation No. 22 of 2021. These findings indicate that land application activities may influence water quality and therefore require continuous environmental management and monitoring.